Experimental and Numerical Simulations of Sediment in Fusre River Basin, Nepal - K.C., Prakash; Baral, Suresh; Mishra, Binaya Kumar; Timilsina, Indra Prasad (Himalayan Journal of Applied Science and Engineering, 2022)
This study presents about the analysis of sediment generation of the ungauged basin Fusre basin by modeling and also with the help of rainfall simulator. Many rivers in Nepal are either ungauged or poorly gauged due to extreme complex terrains, monsoon climate and lack of technical and financial supports. The Soil and Water Assessment Tool (SWAT) was applied for watershed delineation of the Fusre basin and the basin delineated into seven sub-basin that generate the river network, which also provides the information like stream link, stream order, stream length, slope etc. The calibration was performed using data from 2003 to 2010 and validation for the period from 2011 to 2015 at a daily time step. The model performance was evaluated based on computed statistical parameters. For the calibration period of the discharge and sediment flow, the performance of the model was very good, with a coefficient of determination R2= 0.9528, Nash-Sutcliffe Efficiency NSE = 0.942, RMSE = 0.24, and Percent Bias= 14.78, Similarly, the continuous model performance for the validation period was good, with R2 = 0.8655, NSE = 0.925, RMSE = 0.275 and Percent Bias = 18.03. Also a series of laboratory experiments was also carried out by changing the land use, soil parameter, and rainfall intensity by varying depth of soil sample and slope for comparative study with model but just for performance of apparatus. The performance of rainfall simulator was good. From the experimental method the calculation value of coefficient of determination R2 is equal to 0.67, NSE value is equal to 0.865 and PBIAS was equal to 30. The performance of both experimental and simulated data was satisfactory.